Teaching mathematics with technology at kindergarten: resources and orchestrations - Gueudet, Ghislaine; Bueno-Ravel, Laetitia; Poisard, Caroline (The mathematics teacher in the digital era, 2014)
In this chapter we study the use of software by kindergarten teachers in mathematics, with 5 or 6-year-old students. In most countries (our study takes place in France), technology is not much used in the teaching of mathematics at kindergarten and primary school levels. Analysing the conditions, and factors, influencing its use in class is likely to contribute to the study of this - difficult - integration in the teachers' practices (Poisard, Bueno-Ravel, & Gueudet 2011). We retain here a perspective of mediated activity (Vygotsky, 1978), considering that teachers are engaged in a professional activity, with specific objectives, and that the interactions with tools, in the course of this activity, are central. Nevertheless, instead of speaking of 'tools', we focus here on interactions between teachers and various kinds of resources (Gueudet & Trouche, 2009), including technology. We study orchestrations (Drijvers, 2012) set up by kindergarten teachers in class. What are the features of these orchestrations, and which factors determine these features?